Esquizofrenia: psiquiatria, psicanálise e esquizoanálise - diferentes territórios, diferrentes esquizos - Cidade, Fabio Eduardo Umeki (2007)
This dissertation studies the question of squizofrenia through three difrente theories: The psychiatry , the psychoanalysis and the squizoanalysis. The methodology used is the production of sense, as proposed by Deleuze. The sense is a transversal of three propositions: The designation, the manifestation and the meaning. The squizofrenic is used by the psychiatry to develop a medical treatment. In psychoanalysis the squizofrenic is used to mark the failure of the Oedipus complex. In the squizoanalysis the squizofrenic is a role model for a new theory of desire, sustained by the excess. At the end of this dissertation, the control society and the disciplinary society is discussed by the movie PI by Darren Aranofski